If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12(x + -2) + 7(y + 1) = 25 Reorder the terms: 12(-2 + x) + 7(y + 1) = 25 (-2 * 12 + x * 12) + 7(y + 1) = 25 (-24 + 12x) + 7(y + 1) = 25 Reorder the terms: -24 + 12x + 7(1 + y) = 25 -24 + 12x + (1 * 7 + y * 7) = 25 -24 + 12x + (7 + 7y) = 25 Reorder the terms: -24 + 7 + 12x + 7y = 25 Combine like terms: -24 + 7 = -17 -17 + 12x + 7y = 25 Solving -17 + 12x + 7y = 25 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '17' to each side of the equation. -17 + 12x + 17 + 7y = 25 + 17 Reorder the terms: -17 + 17 + 12x + 7y = 25 + 17 Combine like terms: -17 + 17 = 0 0 + 12x + 7y = 25 + 17 12x + 7y = 25 + 17 Combine like terms: 25 + 17 = 42 12x + 7y = 42 Add '-7y' to each side of the equation. 12x + 7y + -7y = 42 + -7y Combine like terms: 7y + -7y = 0 12x + 0 = 42 + -7y 12x = 42 + -7y Divide each side by '12'. x = 3.5 + -0.5833333333y Simplifying x = 3.5 + -0.5833333333y
| y=55x+200 | | (-3u+3)x(u^3-1)= | | y=17(4)-28 | | 2(2x+4)=3x+1 | | -4z+24=-3z-6 | | 12x+5=3x+19 | | x+2x+27+x=163 | | -(x-4)=-1 | | -10(x+4)=9 | | -11=17x-28 | | 5(8x+8)-2(2-7x)=12+55x | | 48y-63=37y+55 | | x-1.5y=-3 | | 16=10+3m | | 8y+1=-31 | | 4x^2+18x= | | 7(2+x)=3x+1 | | -6(k-2)-(-7k+1)=3 | | .5x-12=-14 | | 2y-6+4y-8=0 | | (x+2)+(27+x)=163 | | ln(x)-ln(x-1)=ln(x+3)-ln(x+5) | | 7y-(11-4y)=6 | | 43=26+e | | -2a+5a-13+12= | | 8.50t=51 | | 18+3-2y=5y+3y | | y=17(-3)-28 | | -5/3 | | -7x+11=32 | | 2n+11=-23 | | 5xy+21x=36y+216 |